Diet quality and associated factors among elementary school students of the Adventist school system in the Southwest region of São Paulo, Brazil - Fuentes, Hazel Yvette; Silva Pereira, Taísa Sabrina; Portes, Leslie Andrews; Fortes de Oliveira, Kevin; Teixeira Martins, Márcia Cristina (Población y Salud en Mesoamérica, 2016)
Objective: to evaluate the association between diet and socioeconomic and demographic factors among elementary school students. Methods: A cross-sectional study, involving a random sample of 256 children of both genders, aged between six to eleven years, from grades first through fifth of seven Adventist elementary private schools located in the southwest region of São Paulo State. These schools enroll students independent of their religion. Socioeconomic and demographic data were obtained through a self-administered questionnaire sent home and completed by the parent or legal guardian. The diet quality was assessed through ALES index. Crude and adjusted odds ratios were calculated and logistic regression was used to analyze the variables. Results: Of the sample, 33.2% showed a poor ALES index score and 66.8% had a good score. There were no statistically significant differences between diet quality and the following variables: age, socioeconomic status, maternal level of education, head of household, maternal employment outside the home, exclusive breastfeeding up to 6 months, and origin of school snacks. The variables that remained associated with a good diet quality were: being female (OR = 0.53; 95% CI, 0.30-0.92) and being Adventist (OR = 2.52; 95% CI, 1.10-5.78). Conclusions: The factors associated with good diet quality were gender and religion.